Structural Assimilation of the Bugis Community with the Native on Kangean Island - Emma Rahmawati Fatimah; Ni Made Savitri Paramita; Santi Andayani (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
The Kangean Islands, Madura, serve as a transit hub for traders and fishermen from various regions, including the Bugis ethnic that migrated to the Kangean Islands in the past few decades. Interaction and adaptation carried out by the Bugis ethnic and native in the Kangean islands is able  to bridge the differences between these ethnicities.This article analyses the structural assimilation of the Bugis  community with the natives on the Kangean island, especially at the grassroots level. This research  used the fenomenology approach. Data collection is conducted through in-depth interviews. The findings proved that the process of cultural assimilation of Sulawesi culture in Kangean island, particularly in the Arjasa sub-district can be considered successful, especially when observing the limited conflicts that occur. Structural assimilation has reached a broader scale, encompassing the participation of Bugis community in various aspect. In education, interactions with Bugis culture primarily occur informally in activities organized by the Sulawesi Student Association. In economic, structural assimilation is evident in the mutual acceptance of job opportunities and interdependence in economic resources. Within governmental institutions and organizations, assimilation is achieved by building awareness and understanding of ethnic diversity, maintaining a balance of governance rights between Kangean and Bugis people.  The Kangean Islands, Madura, serve as a transit hub for traders and fishermen from various regions, including the Bugis ethnic that migrated to the Kangean Islands in the past few decades. Interaction and adaptation carried out by the Bugis ethnic and native in the Kangean islands is able  to bridge the differences between these ethnicities.This article analyses the structural assimilation of the Bugis  community with the natives on the Kangean island, especially at the grassroots level. This research  used the fenomenology approach. Data collection is conducted through in-depth interviews. The findings proved that the process of cultural assimilation of Sulawesi culture in Kangean island, particularly in the Arjasa sub-district can be considered successful, especially when observing the limited conflicts that occur. Structural assimilation has reached a broader scale, encompassing the participation of Bugis community in various aspect. In education, interactions with Bugis culture primarily occur informally in activities organized by the Sulawesi Student Association. In economic, structural assimilation is evident in the mutual acceptance of job opportunities and interdependence in economic resources.Within governmental institutions and organizations, assimilation is achieved by building awareness and understanding of ethnic diversity, maintaining a balance of governance rights between Kangean and Bugis people.